Longitudinal associations between leisure activities and subjective happiness among middle-aged and older adults people in China: national cohort study - Feng, Chengkai; Shi, Zhenguo; Tian, Yuge; Ma, Chao; Sun, Qian (Frontiers in Public Health, 2024)
Leisure activities serve as key measures to enhance the subjective happiness of middle-aged and elderly individuals and to positively address the challenges of an aging society; however, the trajectory of changes in their participation in leisure activities and how these changes relate to shifts in subjective happiness have not been adequately explored.This study selected data from the China Health and Aging Longitudinal Study (CHARLS), which included a total of 5,190 middle-aged and elderly people. Linear and nonlinear latent growth models, parallel latent growth models and cross-lagged models were constructed to investigate the influence and lagged relationship between the trajectory of changes in the level of participation in leisure activities on the trajectory of changes in the subjective well-being of middle-aged and elderly people.The initial level of physical activity participation of middle-aged and elderly people significantly predicted the initial level (β=1. 203, p<0.001) and rate of change